GESTÃO DE IDEIAS EM PRÁTICAS DE INOVAÇÃO ABERTA - Stankowitz, Rosângela F.; de Carvalho, Hélio Gomes; Strahus, Faimara do Rocio; Dergint, Dario (European Scientific Journal, ESJ, 2014)
The ideas are part of the early stages of innovation processes. The challenge is to capture them in the most diverse sources of knowledge available beyond the company limits and transforms them into innovative projects that provide return. Cooperation networks are formed with universities, suppliers and other companies via the platforms on the Internet, to identify new opportunities. The aim of this paper is to identify the open innovation actions used by companies to capture and select ideas for innovation. For this, a literature review was done by selecting six Brazilian companies identified as cases of innovation. This paper consists of a brief introduction on the importance of ideas as innovation strategy. The next section deals with the management of open innovation on the transaction of knowledge and technologies, collaborative initiatives with external networks, distinguishing the two models of innovation, open and closed in function of mechanisms of absorption and offer of technologies to increase the success rate of innovations. The mains results indicates that Brazilian companies need to restructure their innovation actions opening their processes through collaboration, internalization and externalization of ideas to reduce risks and increase their competitiveness. Two of the six companies, still practice the closed innovation. The others seek external sources, such as customers, suppliers, universities and patents, new ideas and information for their innovation processes.